Enantioselective Construction of Vicinal Tetrasubstituted Stereocenters by the Mannich Reaction of Silyl Ketene Imines with Isatin‐Derived Ketimines1. Issue 1 (7th November 2014) - Zhao, Jiannan; Fang, Bing; Luo, Weiwei; Hao, Xiaoyu; Liu, Xiaohua; Lin, Lili; Feng, Xiaoming
Abstract A highly enantioselective Mannich reaction of silyl ketene imines with isatin‐derived ketimines has been realized by using a chiral N, N′‐dioxide/ZnII catalyst. A variety of β‐amino nitriles containing congested vicinal tetrasubstituted stereocenters were obtained with excellent outcomes (up to 98 % yield, >19:1 d.r. and 99 % ee). Based on the experimental investigations, a possible transition state has been proposed to explain the origin of the asymmetric induction.